2016
DOI: 10.3390/systems4030031
|View full text |Cite
|
Sign up to set email alerts
|

Ship Routing with Pickup and Delivery for a Maritime Oil Transportation System: MIP Model and Heuristics

Abstract: This paper examines a ship routing problem with pickup and delivery and time windows for maritime oil transportation, motivated by the production and logistics activities of an oil company operating in the Brazilian coast. The transportation costs from offshore platforms to coastal terminals are an important issue in the search for operational excellence in the oil industry, involving operations that demand agile and effective decision support systems. This paper presents an optimization approach to address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
(81 reference statements)
0
14
0
2
Order By: Relevance
“…Rodrigues et al. () studied a maritime routing and scheduling problem of oil cabotage ships between offshore platforms and coastal terminals, also motivated by the actual operation of an oil company operating on the Brazilian coast. Unlike the present multiship routing and scheduling problem with constraints on inventory levels, the problem was formulated as a PDPTW with known quantities to be collected from each platform and delivered to each terminal within time windows, which minimizes costs of fuel consumption of ships and freighting contracts.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al. () studied a maritime routing and scheduling problem of oil cabotage ships between offshore platforms and coastal terminals, also motivated by the actual operation of an oil company operating on the Brazilian coast. Unlike the present multiship routing and scheduling problem with constraints on inventory levels, the problem was formulated as a PDPTW with known quantities to be collected from each platform and delivered to each terminal within time windows, which minimizes costs of fuel consumption of ships and freighting contracts.…”
Section: Related Workmentioning
confidence: 99%
“…These due dates are predetermined using a simple procedure described in Rodrigues et al. (); each TjpkDcorresponds to the end of the time window of terminal j in request ( i, j, p, k ). In this procedure, time windows for the platform and terminal of each request are calculated based on the platform storage capacity, platform production rate, and load quantity of the request previously computed.…”
Section: A Matheuristic Approachmentioning
confidence: 99%
“…Furthermore, a vessel cannot moor on certain platforms or terminals, due to physical issues such as the draft (which is the submerged part of a vessel) and LOA (length overall). Further information about the physical characteristics of the vessels considered in this study can be found in Rodrigues et al (2016).…”
Section: Problem Descriptionmentioning
confidence: 99%
“…More details about this function can be obtained in Rodrigues et al (2016). Constraints (2) ensure that exactly one arc leaves from node i and constraints (3) guarantee that there is exactly one arc that enters j; both ensure that each node is visited exactly once.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…A relax-and-fix heuristic is also explored using the GAMS/CPLEX optimization package, with a view to capturing business requirements and specific aspect of the company's operations. Although there are other related works in the literature along this strand of research, authors are not aware of other studies exploring optimization models and solution methods addressing this pickup and delivery problem with all its particular operating features, except for our other work in Rodrigues (2016) that also proposed a time decomposition heuristic procedure for this problem. These studies were conducted in strong collaboration with a Brazilian oil company, so that the problem could be well defined both in the terms of market characteristics and validity of practical operations.…”
Section: Introductionmentioning
confidence: 99%